Penerapan Metode Tahsin dan Tahfidz UMMI untuk Meningkatkan Hasil Belajar Al-Qur'an Bagi Siswa di MI Muhammadiyah 27 Surabaya - Imam Subeki Firmanto (Bunayya: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2026)
The value of being able to accurately and properly read (tahsin) and memorize (tahfidz) the Qur'an in accordance with the principles of tajwid as a component of Islamic education. In learning the Qur'an, the UMMI technique employs a systematic, organized, and high-quality approach. This study examines the implementation of the tahsin and tahfidz Al-Qur'an curriculum using the UMMI approach and its impact on enhancing Qur'an learning outcomes at MI Muhammadiyah 27 Surabaya. This study employs a descriptive research methodology with a qualitative approach. The methods for collecting data include documentation, interviews, and observation. The study participants are the headmaster, the teachers who oversee the UMMI program, and the pupils. Data reduction, data presentation, and conclusion-drawing are the methods used for data analysis. According to the study's findings, the UMMI approach has been used successfully at MI Muhammadiyah 27 Surabaya to carry out the tahsin and tahfidz program in accordance with the established standards, including planning, implementation, and evaluation of learning. This program is conducted regularly by dividing students into groups according to their skills, using the UMMI handbook, and using a quantifiable evaluation methodology. Additionally, students' Quranic education results improved, as seen by their increased ability to recite the Quran fluently, a greater comprehension of Tajweed, and an increase in the number of Quranic recitations they have memorized. This study's conclusion is that the UMMI method of tahsin and tahfidz program is successful in enhancing students' Quranic learning outcomes. For this reason, this curriculum may serve as a suggested Quranic learning model for use in Islamic elementary schools.